2017
DOI: 10.1113/jp274165
|View full text |Cite
|
Sign up to set email alerts
|

The plasticity of descending controls in pain: translational probing

Abstract: Descending controls, comprising pathways that originate in midbrain and brainstem regions and project onto the spinal cord, have long been recognised as key links in the multiple neural networks that interact to produce the overall pain experience. There is clear evidence from preclinical and clinical studies that both peripheral and central sensitisation play important roles in determining the level of pain perceived. Much emphasis has been put on spinal cord mechanisms in central excitability, but it is now … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
120
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 61 publications
1
120
0
4
Order By: Relevance
“…Catecholamines like norepinephrine and epinephrine signal through the α2-adrenergic receptors (Vo & Drummond, 2016) concentrated in the spinal cord to produce an inhibitory effect. Neurons of the dorsal horn in the spinal cord are directly inhibited by serotonin (from serotoninergic neurons) which, through its action on facilitatory spinal 5-HT3 receptors, influences the expression of CPM (Bannister & Dickenson, 2017). Measures of monoamines in men before a prostate surgery, the levels of monoamines, particularly adrenergics, was correlated to the efficacy of CPM (Parent et al, 2015).…”
Section: A Few Other Pharmacological and Therapeutic Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Catecholamines like norepinephrine and epinephrine signal through the α2-adrenergic receptors (Vo & Drummond, 2016) concentrated in the spinal cord to produce an inhibitory effect. Neurons of the dorsal horn in the spinal cord are directly inhibited by serotonin (from serotoninergic neurons) which, through its action on facilitatory spinal 5-HT3 receptors, influences the expression of CPM (Bannister & Dickenson, 2017). Measures of monoamines in men before a prostate surgery, the levels of monoamines, particularly adrenergics, was correlated to the efficacy of CPM (Parent et al, 2015).…”
Section: A Few Other Pharmacological and Therapeutic Applicationsmentioning
confidence: 99%
“…Pharmacological treatments engaging descending noradrenergic and serotonergic control pathways have shown some efficacy in the treatment of pain, demonstrating the importance of serotonin and norepinephrine in pain modulation (Bannister & Dickenson, 2017; Kirkpatrick et al, 2015). Antidepressants such as tricyclic antidepressants, serotonin–norepinephrine reuptake inhibitors and selective serotonin reuptake inhibitors are used for pain management in chronic pain conditions such as neuropathic pain, migraines, and fibromyalgia (Dharmshaktu, Tayal, & Kalra, 2012).…”
Section: A Few Other Pharmacological and Therapeutic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The human counterpart measure, now referred to as conditioned pain modulation (CPM), is considered to be the psychophysical outcome of activating DNIC, and has received renewed interest in recent years as a sensory testing tool. CPM/DNIC likely reflect the net balance between descending inhibitory and facilitatory signalling; hence, the study of DNIC in rodents represents a useful translatable measure linking pre‐clinical and clinical investigations (Bannister & Dickenson, ). Inefficient CPM might provide insight into underlying pathophysiological mechanisms, and disturbances have been reported in neuropathic pain, irritable bowel syndrome, cluster headache and fibromyalgia (Albusoda et al., ; Kosek & Hansson, ; Perrotta et al., ; Yarnitsky, Granot, & Granovsky, ).…”
Section: Introductionmentioning
confidence: 99%
“…The higher rs-FC between the THA and the PAG may relate to the neuronal facilitation of pain input into the central nervous system (Staud, 2012; Truini et al, 2016; Potvin & Marchand, 2016). Previous studies have found several brain regions such as the PAG, INS, FP, AMYG, hypothalamus, and RVM, are involved in the descending pain modulatory system (DPMS) (Tracey et al, 2007; Henderson & Keay, 2017; Chen et al, 2017; Bannister & Dickenson, 2017). Thus, a higher rs-FC between the brain stem and the THA may support the hypothesized facilitation of pain perception, though functional connectivity does not convey directionality or the type of neuronal function involved (excitation or inhibition) (Rogers et al, 2007; Vattikonda et al, 2016).…”
Section: Discussionmentioning
confidence: 99%